Egina, Argo e l'"agone locale di Era" (Pind. P. 8,79) - Prodi, E (Pàtron Editore, 2018)
This article reassesses Pind. P. 8,79 and schol. ad l. 113c Dr., arguing that the scholion does not testify to an Aeginetan festival in honour of Hera and that Pindar refers to a victory in the Argive Hekatombaia.